Antiviral Activity of Brazilian Propolis from Stingless Bees Against Rotavirus - Guadalupe González-Ochoa; Ana Paola Balderrama-Carmona; Jesús Antonio Erro-Carvajal; José Guadalupe Soñanez-Organis; Luis Alberto Zamora-Álvarez; Marcelo Andrés Umsza Guez (Microorganisms, 2025)
Group A rotavirus (RV) causes gastrointestinal disease in infants worldwide, and there is currently no specific treatment to eliminate the virus. Due to its chemical properties, propolis is a promising compound for improving gastrointestinal infections. This study aimed to evaluate the action of stingless bee propolis against RV. The method involved determining the concentrations of the extracts that do not exhibit cytotoxicity in colon adenocarcinoma cells using the MTT assay and measuring the reduction in infectivity through a focus forming assay. The results showed that stingless bee propolis was non-cytotoxic up to 200 µg/mL. The reduction in RV infectivity exceeded 99% when using propolis from Plebeia droryana and Melipona quadrifasciata. Brazilian stingless bee propolis, whose active components are known for their activity against various viruses, was experimentally tested and demonstrated effective antiviral activity against RV, supporting its potential application as an antiviral agent.